A mulher nas crônicas de José Simão: um estudo da construção dos estados de violência - Jesus, Márcia de Oliveira (2008)
The purpose of this dissertation is to analyze how does language, in its different manifestations, constitute one of the utmost expressive ways of violence in the newspaper Folha de S. Paulo, being such newspaper considered one of the most prestigious and trustful mass communication in Brazil. Specifically, our survey aims demonstrating how the expressions of violence against women are constructed in José Simão s chronicles. Marked, mostly, by a grotesque and inelegant humor, Simão s texts embrace issues that cover from economics and politics to sports and entertainment. Through an apparent adrift chat, the amusement postulated by José Simão s chronicles seem to nullify the violence that when considered something non serious allows that, through it, one does and says things that outside that context, social rules would not allow. In this survey one noticed that the violence forms against women in José Simão s chronicles have been rooted for long time in the core of our sexist and patriarchal society, becoming visible, yet also invisible, because hidden under the form of laws, racism, intolerance, habits and traditions. Whilst reproducing old generalizing and prejudiced stereotypes that deal with the female universe, the author contributes - very much - to violence dissemination and perpetuation that abases women on daily basis. We prove that the woman s image is violently antagonized, turning motif of depreciation and mockery. For the exam of our corpus, we consider as analysis categories, the violence consummated against women, either because of her physical form or because of cultural and social aspects, or her moral quality. The corpus was divided in accordance with those three categories. In linguistic terms, violence against women can be felt by the poly-semantic exploration expressed in the chronicles, not only using metaphors and ironies, but also using depreciatory terms, ambiguities, malicious change of first names and neologisms